BS25 Human macrophages are immunoprofiled by pericardial fluid small extracellular vesicles modulating lipid metabolism mechanisms. (6th June 2022) - Ben-Aicha, Soumaya; Anwar, Maryam; Punjabi, Prakash; Behmoaras, Jacques; Emanueli, Costanza
Abstract : Background: The incidence and severity of ischemic heart disease (IHD) is exacerbated by coronary artery disease (CAD). Monocytes and macrophages are central to atherosclerosis. Endogenous small extracellular vesicles (sEVs) can shuttle microRNAs and other molecular cargos from cell to cell, mediating expressional and functional response in the recipient cells. Recent evidence supports a role for sEVs in modulating macrophage phenotype. The pericardial fluid (PF) is in direct contact with the epicardium and contain sEVs. We recently showed that human PF-sEVs are capable to modulate cardiovascular cells via microRNA shuttling (C.Beltrami et al.2017). Purpose: This study sought to investigate whether PF-sEVs regulate macrophages, contributing to a specific immunophenotype in CAD patients. Methods: PF was collected from either CAD patients undergoing coronary bypass surgery (CABG) or non-atherosclerotic patients operated for mitral valve repair (non-CAD control group). sEVs were isolated using size exclusion chromatography and characterised for size (Nanosight tracking analysis; NTA), tetrasapanin content (by Nanoview chips), microRNA content by RNA seq and proteomic analysis. Monocytes from healthy donors were isolated from buffy coats and differentiated into macrophages following established protocols. Macrophages were incubated with either CAD-sEVs or non-CAD sEVs for 24h at 37oC. The cells were collected and processed for mRNA analyses (qRT-PCR) and flow cytometry. Human PF-cells were isolated and analysed to be compared with the in vitro setting. Further bioinformatics were employed to understand functional pathways and validated in PF from patients. Results: Exposure to CAD-sEVs induces a proinflammatory profile of human macrophages. CAD-sEVs treated macrophages showed a CD36+low, CD206+low CD40+high profile. While non-CAD-sEVs did not statistically differ from PBS nor untouched groups, CAD-sEVs increased the mRNA level of IL1a, IL1b, TNFa and decreased MRC1. Proteomics revealed that PF-sEVs from CAD patients carried higher amounts of pro-inflammatory molecules (ICAM-1 and IL18) compared to NonCAD control. Bioinformatics analysis showed that 861 miRNAs were decreased in the PF-sEVs from CAD patients compared to non-CAD. miRNA targets prediction and pathway analyses reported that clusters of deregulated miRNAs could regulate CD36 and SRB1 which were shown to be decreased in CAD-sEVs treated macrophages. Human PF-cells revealed a reduced expression of CD36 on PF-macrophages. Conclusions: We demonstrate, for the first time, that sEVs isolated from the PF of CAD patients induce a proinflammatory profile of human macrophages and that target crucial lipid metabolism pathways. These clinically relevant results could drive to decipher improved therapeutics able modulate the epicardial/myocardial immune response in CAD patients.